Implementation of Risk Management in an Effort to Realize the Good University Governance Principles - Permana, Nalendra Bhayu; Haliah, Haliah; Kusumawati, Andi; Pertiwi, Meilani Intan; Ihlashul’amal, Muhammad (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2024)
This study examines the implementation of risk management at Hasanuddin University in its efforts to realize Good University Governance (GUG) principles, such as transparency, accountability, and efficiency. Using a qualitative approach, data were collected through in-depth interviews, document analysis, and observations involving key university stakeholders. The findings show that while the university has established formal risk management frameworks, several challenges persist. These include resource limitations, inconsistent communication between departments, and a lack of a risk-aware culture. Despite these obstacles, the implementation of risk management has contributed positively to enhancing transparency and accountability by providing systematic processes for identifying, assessing, and mitigating risks. However, full integration with the broader governance system remains incomplete. To fully leverage risk management in supporting GUG principles, the university must promote greater stakeholder involvement, improve resource allocation, and ensure stronger alignment between risk management and governance strategies. These findings offer valuable insights for higher education institutions aiming to enhance governance through effective risk management.